Penafsiran La'nat dalam Qs Al-Baqarah Ayat 161: Studi Muqaran Tafsir Ath-Thabari dan Tafsir Al-Qurthubi - Dede Febriani; Ahmad Deski; Febri Wardani; Irpan Rambe (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study examines the interpretation of la'nat (curse/condemnation) in QS Al-Baqarah verse 161 through a comparative analysis of two authoritative classical exegetical works: Tafsir Jami' Al-Bayan fi Ta'wil Al-Qur'an by Imam Muhammad ibn Jarir al-Thabari and Al-Jami' Li Ahkam Al-Qur'an by Imam Abu Abdillah Muhammad al-Qurthubi. The central problematic concerns how each mufassir conceptualizes and articulates la'nat a term that appears 41 times across 36 verses and 18 surahs of the Quran specifically as it relates to those who die in a state of disbelief. Employing a library research design with the muqaran(comparative) methodology, the studyrelies primarily onthe two tafsir works as main sources, supplemented by relevant secondary literature. The findings reveal meaningful interpretive distinctions: Ath-Thabari understands la'nat from Allah as the banishment from divine mercy, while la'nat from the angels and humanity is interpreted as a collective supplication invoking divine punishment upon wrongdoers; Al-Qurthubi, by contrast, frames la'nat as a manifestation of divine condemnation accompanying death in disbelief, with la'nat from the angels and people constituting an expression of righteous indignation against kufr. Despite these differences, both scholars converge on the point that la'nat from the angels and humanity functions as a verbal act either prayer or declaration directed against those who transgress divine law. The study concludes that the two classical commentators, though separated by centuries and different geographic and intellectual contexts, arrive at a shared fundamental conviction that dying in a state of disbelief carries grave and irreversible spiritual consequences.